Availability of literature on social entreprenureship for sustainable wealth creation in internet - Benjasom, Muhammad Husnee; Ismail, Yusof; Mhd. Sarif, Suhaimi (2012)

(untitled)
Social entrepreneurship has been the key discussed issue for the last few decades. This paper examines relative availability of materials related to social entreprenureship for sustainable wealth creation in order to develop hands-on, professional, ethical, which is promoted by the various organizations around the world. The main objective of this study was to examine the relative frequency of social entreprenureship and sustainable wealth creation by the organizations and other related concepts that are available in the Internet search engines. The study attempted to assess the availability of materials on social entreprenureship for sustainable wealth creation on the Internet. The Internet was accessed on 03 April 2012 from 11:05 a.m. – 13:05 p.m.; 2.30 p.m. – 4:30 pm. Duration: 240 minutes, [Gombak Time] and 04 April 2012 from 9:30 a.m. – 11:00 a.m.; 11:30 p.m. – 1:00 p.m. Duration: 180 minutes [Hulu Langat Time]. Ratios are expected to reflect more statistically meaningful indices. The study is very significant for theoretical development of social entreprenureship in sustainable wealth creation for companies in Malaysia. The Internet search engine provides instant information on social entreprenureship for sustainable wealth creation that can developed further.